Impact of HPV vaccination on number of surgical procedures required in recurrent respiratory papillomatosis and its potential use as an adjuvant - Aslam, Mohammed Afeef; Maududi, Yusuf (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
People who suffer from recurrent respiratory papillomatosis have to undergo multiple surgical procedures for debulking resulting in complications such as reduced quality of voice. Data source was Pubmed articles. The objective of this study was to review the current literature on HPV vaccination and its impact on RRP and whether it may help reduce the number of surgical procedures required. Articles from year 2000 onwards were searched for on PubMed. Overall articles show significant increase in surgical intervals post HPV vaccination. HPV vaccination appears to be a safe adjuvant therapy in the management of recurrent respiratory papillomatosis.